Parametric study of pounding tuned mass damper for subsea jumpers. (11th December 2015) - Zhang, P; Li, L; Patil, D; Singla, M; Li, H-N; Mo, Y L; Song, G
Abstract: In previous study, a pounding tuned mass damper (PTMD) was proposed to reduce the undesired vibration of a subsea jumper. Both experimental and numerical results verified the effectiveness of the PTMD. This paper aims to enhance the understanding of the PTMD through a parametric study. The jumper is subjected to sinusoidal forces of different frequencies. The reduction ratio is defined for evaluation of the mitigation performance. Three parameters are considered in this study: the pounding stiffness, the gap between the delimiter and the mass block, and the mass ratio. The parametric studies show that the PTMD system is not so sensitive to the small variations of the pounding stiffness and the gap. The reduction ratio is significantly increased with the mass ratio increased up to 2%. Afterwards, it is not so economic or practically feasible to enlarge the mass ratio.